2015
DOI: 10.1074/jbc.m114.632547
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Mitochondrial Ca2+ Uniporter in the Generation of Mitochondrial pH Gradient and Metabolism-Secretion Coupling in Insulin-releasing Cells

Abstract: Background: Mitochondrial Ca 2ϩ uptake affects energy metabolism and insulin secretion. Results: Knockdown of mitochondrial Ca 2ϩ uniporter decreases respiratory chain activity and mitochondrial pH gradient generation. Conclusion: Mitochondrial Ca 2ϩ uptake via uniporter is essential for oxidative phosphorylation and metabolism-secretion coupling. Significance: The present study identifies mechanisms of action and bioenergetic consequences of mitochondrial Ca 2ϩ transporters in insulin-releasing cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 48 publications
3
58
0
Order By: Relevance
“…[Ca 2ϩ ] m -mediated pyruvate dehydrogenase activation and increased substrate affinity for the other dehydrogenases could thus facilitate cycle operation during the refilling phase. Quan et al (427) provided apparent support for this hypothesis when they observed that basal and glucose-stimulated respiration were both reduced in INS-1E cells following MCU knockdown. However, a surprising complication was that expression levels of electron transport complexes were severely reduced in the knock-down.…”
Section: If the Effect Of Elevated [Ca 2ϩmentioning
confidence: 68%
See 4 more Smart Citations
“…[Ca 2ϩ ] m -mediated pyruvate dehydrogenase activation and increased substrate affinity for the other dehydrogenases could thus facilitate cycle operation during the refilling phase. Quan et al (427) provided apparent support for this hypothesis when they observed that basal and glucose-stimulated respiration were both reduced in INS-1E cells following MCU knockdown. However, a surprising complication was that expression levels of electron transport complexes were severely reduced in the knock-down.…”
Section: If the Effect Of Elevated [Ca 2ϩmentioning
confidence: 68%
“…A similar time course can be seen in the respiratory response of clonal insulinoma cells and human islets to acutely elevated glucose, with an initial doubling of respiration followed by a further increase over the subsequent 50 min (112,184,491). Much of the enhanced proton current is directed through the ATP synthase, rather than the endogenous proton leak, judged by the extent of oligomycin inhibition (FIGURE 3D) (112,147,184,427). To date, I am not aware of any detailed quantitative analysis of the ATPconsuming reactions in the ␤-cell cytosol.…”
Section: If the Effect Of Elevated [Ca 2ϩmentioning
confidence: 75%
See 3 more Smart Citations